Board Characteristics and Information Technology Governance on Cybersecurity Disclosure in Indonesian Banking - Kamillah, Najwa; Rut Damayanti, Cacik; Nugroho Luthfi Imam Fahrudi, Agung (Profit: Jurnal Adminsitrasi Bisnis, 2026)
The escalation of cyber threats in the banking industry necessitates greater transparency of information to ensure the maintenance of the financial system. Nevertheless, there are inconsistencies in the results of previous research and limited studies that collectively integrate board characteristics and digital transparency in Indonesia. This study analyzes the influence of IT expertise, gender diversity, board meetings, and IT governance on cyber security disclosure. This study utilizes a quantitative approach through multiple regression analysis to examine 47 banking sectors listed on the Indonesian Stock Exchange during the 2019-2023 period. The research findings indicate that board meetings and IT governance have a significant positive effect on cybersecurity disclosure, whereas IT expertise and gender diversity do not reveal a significant effect. In accordance with the principles of Upper Echelons Theory, this study provides a theoretical contribution by demonstrating that the level of coordination and management structure are pivotal factors in enhancing cyber transparency. The results of this study have strategic implications for organizations seeking to enhance corporate transparency and cyber risk disclosure.